2022
DOI: 10.1002/cbdv.202100993
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition, Antioxidant Activity, Cholinesterase Inhibitor and in Vitro Insecticidal Potentiality of Essential Oils of Lippia multiflora Moldenke and Eucalyptus globulus Labill. on the Main Carpophagous Pests of Cotton Plant in Ivory Coast

Abstract: The abusive and repeated use of synthetic chemical insecticides has proven to be harmful to human health and the viability of the cotton production system in Ivory Coast, so it is imperative to find alternatives. . Thus, the objective of this study was to study the chemical composition and biological activity of essential oils of Lippia multiflora (Verbenaceae) and Eucalyptus globulus (Myrtaceae) and to evaluate their insecticidal potential in the laboratory on three main pests of cotton. After essential oils … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…Indeed, for all essential oils, increasing concentrations led to an increasing evolution of mortality in the batches of caterpillars. This fact was the same when testing the sensitivity of adults of Pectinophora gossypiella , a carpophagous insect of cotton, with the same essential oils [12–14] . Our observations are in line with those of Akantetou et al.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Indeed, for all essential oils, increasing concentrations led to an increasing evolution of mortality in the batches of caterpillars. This fact was the same when testing the sensitivity of adults of Pectinophora gossypiella , a carpophagous insect of cotton, with the same essential oils [12–14] . Our observations are in line with those of Akantetou et al.…”
Section: Resultssupporting
confidence: 92%
“…This fact was the same when testing the sensitivity of adults of Pectinophora gossypiel-la, a carpophagous insect of cotton, with the same essential oils. [12][13][14] Our observations are in line with those of Akantetou et al. [15] Indeed, these authors revealed the well-marked positive evolution of average mortality rates with increasing concentration of essential oil of O. canum and O. basilicum and regardless of the duration of aphid exposure.…”
Section: Molecular Dockingsupporting
confidence: 91%
See 2 more Smart Citations
“…Any individual that moves and moves normally was considered alive (Doffou, 2012). If mortality in the control batch was greater than or equal to 10%, the test was rejected or when dead or moribund insects were observed among the controls, mortality rates were corrected by the Abbott (1925) formula: T A B L E 1 Composition of the artificial nutrient substrate for rearing H. armigera (Kobenan et al, 2022). As a first approximation, we must admit that the lethal toxic effects, resulting from the contamination of the food, depend on the concentration (C) of the aqueous extracts in it and on the duration of exposure (T) to this concentration, following Haber's law: When there is at least one study of sufficient quality for the exploitation of the experimental results retained for the lethal effects, the model f, will be the statistical model "probit" (Finney, 1971).…”
Section: Data Collectionmentioning
confidence: 99%